Impact of Sawdust and Chicken Manure Compost Mixture on The Growth and Yield of Sallot (Allium ascalonicum L.) - Silvia, Silvia Permata Sari; Herawati, Netti; Nurfalah, Resti; Kusumawati, Aries; Hervani, Dini (Jurusan Budidaya Perkebunan, 2025)
Shallot (Allium ascalonicum L.) is a high-value horticultural commodity in Indonesia, with demand increasing annually. To meet this demand, enhancing both the quality and quantity of shallot production through optimal fertilization is crucial. This study investigates the effect of a compost combination of sawdust and chicken manure on shallot growth and yield. The research was conducted in Nagari Koto Laweh, X Koto Sub-district, Tanah Datar Regency, from May to August 2025. A Randomized Complete Block Design (RCBD) with five treatments and three replications was used in the experiment. Data were analyzed using the F-test and Duncan’s New Multiple Range Test (DNMRT). The results revealed that a 1:3 sawdust-to-chicken manure ratio was the most effective, significantly increasing plant height (41.50 cm), leaf number (45.75 pieces), bulbs count (10.83 bulbs), bulb diameter (29.65 mm), fresh and dry bulb weight per clump (97.15 g/clump), dry bulb weight per hectare (18.11 tons/ha), and pest and diseases (Thrips tabaci, Spodoptera exigua, Delia antiqua, Fusarium oxysporum, Peronospora destuctor, Alternaria porri). These findings indicate that the compost combination not only boosts shallot production but also has the potential for broader application in other crops such as oil palm, sugar palm, and cocoa, offering an eco-friendly alternative to chemical fertilizers and contributing to sustainable agriculture practices by improving soil fertility.